Evaluation of Adhesion and Morphology of Human Osteoblasts to White MTA and Portland Cement - Bidar, Maryam; Tavakkol Afshari, Jalil; Shahrami, Fatemeh (Iranian Endodontic Journal, 2008)
INTRODUCTION: Osteoblasts and periodontal ligament cells are major cells for wound healing after root end resection. The interaction of osteoblasts with filling materials could play a critical role in healing of surgical lesion. Adhesion and spreading of cells on material surface are the initial phase for cellular function. The purpose of the present study was the evaluation of morphology and attachment of human osteoblasts in present of white MTA, Portland cement (PC) and IRM as root end filling and perforation repair materials. MATERIALS AND METHODS: The human osteoblasts (MG-63 cell line) were prepared from Iranian Pasteur Institute; Cellular Bank, were grown in RPMI 1640 medium. The testing materials were mixed according to the manufacture's instruction, inserted in to the wells of 24-well flat-bottomed plate, and condensed to disk of 1mm thickness and 1×1mm diameter. Cells were added to the materials after two weeks. During 1,3,7 days intervals, the disk of materials along with cells were grown on their surface, examined by a scanning electron microscope (SEM). We used of IRM as negative group. RESULTS: Results showed that after 7 days many of osteoblasts were attached on the surface of white MTA and PC and appeared partially round or flat. The cells appeared round with no attachment and spreading in conjunction with IRM. CONCLUSION: The results indicate that human osteoblasts have a favorable response to white MTA and Portland cement compared with IRM.